The Relationship Between Spiritual Well-Being, Life Satisfaction and Hope in Elderly Individuals in Turkey - Özdemir, Aysel A. (Journal of religion and health, 2023)
Life satisfaction and hope are important features in elderly individuals. Spiritual well-being is thought to affect life satisfaction and hope in the elderly. This study was conducted to determine the association between spiritual well-being and life satisfaction and hope in elderly persons. This study followed a cross-sectional design. The sample size of the study was 1383 individuals aged 65 or older. The Spiritual Well-Being Scale (FACIT-Sp), Satisfaction with Life Scale, and Hope Scale were administered to participants. Results indicated that spiritual well-being was significantly associated with life satisfaction and hope (p < 0.05). A limitation of this finding is the possible contamination of the measure of spiritual well-being with indicators of meaning and peace that could explain the relationship between spiritual well-being and hope. The spiritual well-being scale used in this research included indicators of meaning and peace that could explain the relationship between spiritual well-being and hope.